2001
DOI: 10.1016/s0014-2999(01)00745-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of carvedilol in the high-conductance state of the mitochondrial permeability transition pore

Abstract: The mitochondrial permeability transition is a widely studied, but poorly understood, phenomenon in mitochondrial bioenergetics. It has been recognised that this phenomenon is related to the opening of a protein pore in the inner mitochondrial membrane, and that opening of this pore is the cause of some forms of mitochondrial dysfunction. In this work, we propose that carvedilol, a multi-role cardioprotective compound, may act as an inhibitor of the high-conductance state of the mitochondrial permeability tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…The authors attributed the cardioprotection to inhibition of pore opening by carvedilol acting as an antioxidant, as opposed to its β-adrenergic antagonist properties. This conclusion was supported by the demonstration that carvedilol decreased the number of oxidized protein thiol groups in heart mitochondria [169].…”
Section: Inhibition Of Ptp Opening By Free Radical Scavengersmentioning
confidence: 79%
“…The authors attributed the cardioprotection to inhibition of pore opening by carvedilol acting as an antioxidant, as opposed to its β-adrenergic antagonist properties. This conclusion was supported by the demonstration that carvedilol decreased the number of oxidized protein thiol groups in heart mitochondria [169].…”
Section: Inhibition Of Ptp Opening By Free Radical Scavengersmentioning
confidence: 79%
“…Oliveira et al has shown that carvedilol can prevent the MPT in rat heart by inhibiting the formation of high-conductance pores. The underlying mechanism appears to be the prevention of oxidation of membrane thiol groups, which are important in the formation of the MPTP [94,98,99]. Besides the cardioprotective properties described, members of our research team have reported that carvedilol inhibits the exogenous NADH dehydrogenase in rat heart mitochondria [100], which is described to play a key role in the cardiotoxicity of doxorubicin [101].…”
Section: Hemodynamic Drugsmentioning
confidence: 96%
“…Mitochondrial swelling was measured by monitoring the decrease in absorbance at 540 nm [16]. The decrease in absorbance was measured by incubating 9 mg of mitochondrial protein in 3 mL of basic medium D (70 mM sucrose, 213 mM mannitol, 3 mM HEPES, 1 mM EGTA, 10 mM succinate, and 1 μM rotenone); the medium D was adjusted to pH 7.3 with Tris.…”
Section: Mpt Analysismentioning
confidence: 99%